Using Google Classroom as Assistive Technology in Universally Designed Classrooms - Sharpe, Stephen; Young, Gabrielle (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
This study focuses on the use of Google Classroom as assistive technology in inclusive classrooms. Findings were based on data collected through single-case study methodology in semi-structured formal and informal interviews with eight teachers and a focus group with six students at one junior high school in the province of Newfoundland and Labrador in Canada. This study is designed to better understand the benefits and challenges associated with the use of Google Classroom within the framework of universal design for learning. The findings showed that Google Classroom was perceived by both teachers and students as effective classroom technology in meeting the needs of each learner in the classroom.